1997
DOI: 10.1016/s0550-3213(97)00606-8
|View full text |Cite
|
Sign up to set email alerts
|

Classical and quantum aspects of BPS black holes in N = 2, D = 4 heterotic string compactifications

Abstract: We study classical and quantum aspects of D = 4, N = 2 BPS black holes for T 2 compactification of D = 6, N = 1 heterotic string vacua. We extend dynamical relaxation phenomena of moduli fields to background consisting of a BPS soliton or a black hole and provide a simpler but more general derivation of the Ferrara-Kallosh's extremized black hole mass and entropy. We study quantum effects to the the BPS black hole mass spectra and to their dynamical relaxation. We show that, despite non-renormalizability of st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 95 publications
(84 reference statements)
2
19
0
Order By: Relevance
“…We have shown that the solutions of the quantum corrected BPS equations are such that the local central charge always has constant phase as one approaches the center of the monopole. We further showed that this equation can be rewritten in a form analogous to the attractor equation and concluded that we are studying the attractor mechanism with gravity turned off as was previously concluded in [3][4][5].…”
Section: Discussionsupporting
confidence: 55%
“…We have shown that the solutions of the quantum corrected BPS equations are such that the local central charge always has constant phase as one approaches the center of the monopole. We further showed that this equation can be rewritten in a form analogous to the attractor equation and concluded that we are studying the attractor mechanism with gravity turned off as was previously concluded in [3][4][5].…”
Section: Discussionsupporting
confidence: 55%
“…In the following, we study the effect of the quantum correction terms of the prepotential on the classical solutions [123,54,514,50,51].…”
Section: Quantum Aspects Of N = 2 Black Holesmentioning
confidence: 99%
“…The condition that Sl(2, R) is broken down to Sl(2, Z) so that M 2 with the coprime integers {p 1 , p 2 } remains non-singular after the transformation is translated into the type-IIB language that the Sl(2, R) symmetry of the equations of motion is broken down to the Sl(2, Z) S-duality symmetry of type-IIB string theory. In the following we discuss particular cases of (514). We first consider the solution (514) with U = diag(H 1 (x 1 ), H 2 (x 2 )) and H = 1.…”
Section: As An Example Solution For Intersecting R-r (P + R)-brane Amentioning
confidence: 99%
“…The attractor equations can also be obtained from the requirement of conservation of one half of the supersymmetries [4,20,21,22]. Solutions and generalisations have been discussed for example in [20,21,22,23].…”
Section: Bps Solutions: the Attractor Equationsmentioning
confidence: 99%